On the symmetry and exact solutions of a certain transport equation - Popovich, R. O. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
Both the Lie andQ-conditional symmetry of a certain linear transport equation are studied and classes of its exact solutions are obtained.